Improving the Effect of Transcranial Alternating Current Stimulation (tACS): A Systematic Review - Wu, Linyan; Liu, Tian; Wang, Jue (Frontiers in Human Neuroscience, 2021)
With the development of electrical stimulation technology, traditional transcranial alternating current stimulation (tACS) technology has been found to have the drawback of not targeting a specific area accurately. Studies have shown that optimizing the number and position of electrodes during electrical stimulation has a very good effect on enhancing brain stimulation accuracy. At present, an increasing number of laboratories have begun to optimize tACS. However, there has been no study summarizing the optimization methods of tACS. Determining whether different optimization methods are effective and the optimization approach could provide information that could guide future tACS research. We describe the results of recent research on tACS optimization and integrate the optimization approaches of tACS in recent research. Optimization approaches can be classified into two groups: high-definition electrical stimulation and interference modulation electrical stimulation. The optimization methods can be divided into five categories: high- definition tACS, phase-shifted tACS, amplitude-modulated tACS, the temporally interfering method and the intersectional short pulse method. Finally, we summarize the latest research on hardware useful for tACS improvement and outline future directions.